Physicochemical behaviour of artificial lime stabilised sulfate bearing cohesive soils - Buttress, Adam James (2013)
Soil stabilisation is a useful civil engineering technique that enables the insitu material to be used as part of an engineered structure. Stabilised layers are used in road foundation; working platforms and for slope stabilisation and sea defences. Chemical stabilisation involves the use of a hydraulic binder (and sometimes additional pozzolans). Commonly, quicklime (CaO) or slaked-lime (Ca(OH)2) is used. On mixing into the ground, this reacts with the aluminosilicates of the clay fraction, reducing its overall water content and plasticity. Further additions increase the insitu pH. Above pH 10.4, the aluminosilicates become soluble in the pore solution. They are then able to form a range of insoluble mineral hydrates which constitute a cementitious matrix. This results in both an increase in mechanical strength and a decrease in dimensional stability.